Sandbox regulatório nas repactuaç\~oes das concess\~oes federais de infraestrutura de transportes: O caso da Rodovia Eco 101 - Ricardo Sampaio da Silva Fonseca (Instituto de Pesquisa Econômica Aplicada (IPEA), 2025)
– This article investigates the use of regulatory sandboxes - specifically policy-oriented sandboxes - as a tool to support the renegotiation of concession contracts in Brazil's federal transport infrastructure sector. Drawing from the framework of smart regulation and regulatory experimentalism, the study analyzes the case of the Eco 101 Highway concession, where a sandbox was structured to test the market offering of a redesigned contract. The research explores the legal and institutional framework of regulatory sandboxes in land transport, the specific and systemic risks involved in contractual renegotiations, and the regulatory challenges faced. The findings suggest that regulatory sandboxes can offer a controlled environment for mitigating risks and testing new contractual arrangements, provided that institutional safeguards ensure transparency, incentive alignment, and legal stability
Keywords: L51; L92; H54; O38; 330; regulatory sandbox; contract renegotiation; infrastructure concessions; smart regulation; transport sector; roads